1983
DOI: 10.1017/s0021859600038570
|View full text |Cite
|
Sign up to set email alerts
|

The effects of liming and soil pH on carbon and nitrog contained in the soil biomass

Abstract: SUMMARYThe C and N in the biomass of soils from eight grassland field experiments where lime had been applied was determined by the chloroform fumigation method. Lime application increased C and N in the biomass by approximately 30% overall, although there was no effect at two sites. In the unlimed plots basal CO2 production, biomass C, and flush of mineral N production (FN) increased with soil pH. Biomass C and FN were correlated with total N content but not with organic C.Differences in the apparent C/N rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 10 publications
3
28
1
1
Order By: Relevance
“…However, since soils having different natural pHs also differ in many other properties, the effect of soil pH is often investigated by modifying the pH gradually (1,33), typically by the application of lime. This method of pH manipulation can take years, with repeated lime applications being required.…”
Section: Discussionmentioning
confidence: 99%
“…However, since soils having different natural pHs also differ in many other properties, the effect of soil pH is often investigated by modifying the pH gradually (1,33), typically by the application of lime. This method of pH manipulation can take years, with repeated lime applications being required.…”
Section: Discussionmentioning
confidence: 99%
“…For example, early experiments by Christ and David (1996) determined that increased soil temperature and moisture in summer resulted in increased DOC production in the organic horizons of red spruce Spodosols. Soil pH is considered to be a dominant factor controlling the microbial transformation of organic matter (Adams and Adams, 1983;Kemmitt et al, 2006), and a lower soil pH under slash pine favored the accumulation of soil C and thus led to a greater DOC concentration (Shunbao et al, 2012). Table 3.…”
Section: Variations In Doc and Don Concentrationsmentioning
confidence: 99%
“…The presence of an active microflora also influences carbon loss from plants grown in solution culture (Kraffczyk et al, 1984;Lee and Gaskins, 1982) and in soil (Martin and Kemp, 1986;Martin, 1977). Many chemical and biological properties of soil are strongly related to soil pH (Carter, 1986;Adams and Adams, 1983) as in plant growth (Hojito et al, 1987) and it may, therefore, be expected that soil pH will influence the pattern of carbon flow from plant roots. Frenzel (1960), and Lundegradh and Stenlid (1944), reported that the hydrogen ion concentration of the nutrient solution in which plants (sunflower, peas and wheat) were grown had little or no effect on root exudation.…”
Section: Introductionmentioning
confidence: 99%